2020
DOI: 10.3389/fcell.2020.00281
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Pin1 Isomerization of ATR: Its Role in Regulating ATR’s Anti-apoptotic Function at Mitochondria, and the Implications in Cancer

Abstract: Peptidyl-prolyl isomerization is an important post-translational modification of protein because proline is the only amino acid that can stably exist as cis and trans, while other amino acids are in the trans conformation in protein backbones. This makes prolyl isomerization a unique mechanism for cells to control many cellular processes. Isomerization is a rate-limiting process that requires a peptidyl-prolyl cis/trans isomerase (PPIase) to overcome the energy barrier between cis and trans isomeric forms. Pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…[1][2] These systems display an ensemble of conformations instead of ap ermanent secondary structure.T he conformational flexibility enables them to bind to multiple targets and to become potential drug targets. [3][4][5] One factor contributing to the conformational heterogeneity is the cis/trans isomerization of proline (Pro) residues.T he different cis/trans-Pro states are associated with tumorigenesis (in p53TAD [6] and ATR [7] ), the formation of neurodegenerative diseases (in tau [8] and a-synuclein [9] )and in circadian rhythm regulation. [10] Previous studies suggested that the different isomeric forms can inhibit or support protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] These systems display an ensemble of conformations instead of ap ermanent secondary structure.T he conformational flexibility enables them to bind to multiple targets and to become potential drug targets. [3][4][5] One factor contributing to the conformational heterogeneity is the cis/trans isomerization of proline (Pro) residues.T he different cis/trans-Pro states are associated with tumorigenesis (in p53TAD [6] and ATR [7] ), the formation of neurodegenerative diseases (in tau [8] and a-synuclein [9] )and in circadian rhythm regulation. [10] Previous studies suggested that the different isomeric forms can inhibit or support protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In line with that, we observed a decrease in the phosphorylation status of p53 in tAMs stimulated in vitro with GM-CSF, suggesting that upon GM-CSF exposure, the cells are permissive to cell division although DNA damage might be present. Similarly, ATR expression and function may be uncoupled from its mRNA expression via modulation of its phosphorylation status, in particular in the control of DNA damage associated with cell death [ 54 ] or its isomeric status [ 55 ]. In contrast, MafB expression increased upon in vivo HDM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage response (DDR), mediated by p53, eventually activates proteins such as PUMA (p53 upregulated modulator of apoptosis), BAX (Bcl‐2‐associated X protein) and BAK (Bcl‐2 homologous antagonist/killer), thereby yielding the release of pro‐apoptotic factors from mitochondria [6]. Notably, one of the three known DDR early sensors, the ataxia telangiectasia and Rad3‐related (ATR) protein, plays a dual role depending on its isomerization state: one state aids the onset of DDR upstream of p53 in the cell nucleus and the other state plays a protective role against pro‐apoptotic stimuli in mitochondria [7]. This illustrates how mitochondrial reactions can be modulated during the DDR response, but does not imply a direct involvement of mitochondrial proteins in regulation of nuclear DNA repair or DDR.…”
Section: Figmentioning
confidence: 99%